Self-template synthesis of hollow ellipsoid Ni–Mn sulfides for supercapacitors, electrocatalytic oxidation of glucose and water treatment. Issue 16 (7th April 2017) - Cheng, Cheng; Kong, Dechen; Wei, Chengzhen; Du, Weimin; Zhao, Jianbo; Feng, Yeqin; Duan, Qingling
Abstract : Hollow ellipsoid Ni–Mn sulfides have been successfully synthesized via a simple self-template method and exhibited good performance in supercapacitors, electrocatalytic oxidation of glucose and water treatment. Abstract : In this work, we have successfully developed a simple self-template route for preparation of hollow ellipsoid Ni–Mn sulfides. This route involves the synthesis of solid Ni–Mn ellipsoids via a chemical precipitation method. Then, using thioacetamide (TAA) as the sulfur source, the solid Ni–Mn ellipsoids can be easily converted to hollow ellipsoid Ni–Mn sulfides in ethanol via sulfidation reaction. The as-synthesized hollow ellipsoid Ni–Mn sulfides possess large specific surface areas and porous structures. Benefiting from these structural and compositional advantages, the electrochemical performance of the hollow ellipsoid Ni–Mn sulfides is studied. As expected, the hollow ellipsoid Ni–Mn sulfides show a high specific capacitance of 1636.8 F g −1 at 2.0 A g −1 and good cycling stability (only 4.9% loss after 4000 cycles) as electrode materials for supercapacitors. Furthermore, electrocatalytic oxidation of glucose based on the synthesized hollow ellipsoid Ni–Mn sulfides is also performed. The hollow ellipsoid Ni–Mn sulfides present high sensitivity and selectivity, good stability and a low detection limit (0.02 μM). In addition, the as-synthesized hollow ellipsoid Ni–Mn sulfides exhibit good ability to remove the Congo red dyes from water, which gives them potential application in water treatment. The current work makes a major contribution to the design and preparation of hollow metal sulfide structures, as well as their potential applications in supercapacitors, electrocatalytic oxidation of glucose and water treatment.